2014
DOI: 10.1002/chem.201402564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Electronic Influences Imposed by Substituent Variation in Polyazine‐Bridged Ruthenium(II)/Rhodium(III) Supramolecules

Abstract: Unusual and unprecedented multipathway electrochemical mechanisms for a new class of supramolecular Ru/Rh bimetallic photocatalysts have been uncovered. The near isoenergetic Rh(dσ*) and bridging ligand(π*) molecular orbitals and a rate of halide loss that occurs on the cyclic voltammetry timescale provide a series of closely related complexes which display four different electrochemical mechanisms. A single complex displays two concurrent electrochemical pathways in marked contrast to all previously studied c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…This behavior, in which the first reduction is ligand-localized but a second reduction yields Rh­(I) and the neutral bridging ligand is known for bimetallic Rh­(III) and Ir­(III) complexes in which [M III ( BL – )­M III ] + e – → [M III (BL 0 ) M I ] . A two-step reduction was observed for Ru,Rh bimetallic complexes with the ratios of current for each step dependent on the rate of halide dissociation . In contrast, our chloride detection experiments verify the stability of the Rh­(III) coordination environment in the singly reduced species.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This behavior, in which the first reduction is ligand-localized but a second reduction yields Rh­(I) and the neutral bridging ligand is known for bimetallic Rh­(III) and Ir­(III) complexes in which [M III ( BL – )­M III ] + e – → [M III (BL 0 ) M I ] . A two-step reduction was observed for Ru,Rh bimetallic complexes with the ratios of current for each step dependent on the rate of halide dissociation . In contrast, our chloride detection experiments verify the stability of the Rh­(III) coordination environment in the singly reduced species.…”
Section: Resultssupporting
confidence: 57%
“…79 A two-step reduction was observed for Ru,Rh bimetallic complexes with the ratios of current for each step dependent on the rate of halide dissociation. 80 In contrast, our chloride detection experiments verify the stability of the Rh(III) coordination environment in the singly reduced species. Wave F (−1.04 V) is assigned to the (μ-Ru,Rh I -dpp) 0/− couple of the Rh(I) complex by comparison to the nonbridging ligand potential of Ru 3 while two C waves (−1.16, −1.32 V) are assigned as the second reductions of the (μ-Ru,Ru-dpp) ligands similarly to Ru 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…The reductive properties of the Ru­(II),Rh­(III) bimetallics (Figure ) are considerably more complex than the Ru­(II) monometallic counterparts, expected to possess dpp 0/– and Rh III/II and Rh II/I reductions prior to bpy 0/– reductions. Three separate reduction processes, −0.38, −0.72, and −0.99 V vs Ag/AgCl, are observed and attributed to Rh III/II , Rh II/I , and dpp 0/– reductions, demonstrating the energetic proximity of the Rh­(dσ*) and dpp­(π*) orbitals in this bimetallic motif. To confirm the assignment of these reduction processes, a study was performed by White et al using a set of nearly identical Ru­(II),Rh­(III) bimetallics, differing only in the terminal ligands . It was found that the first two reductions displayed electrochemical irreversibility, indicating an electrochemical reduction followed by rapid halide loss.…”
Section: Resultsmentioning
confidence: 98%
“…58−60 To confirm the assignment of these reduction processes, a study was performed by White et al using a set of nearly identical Ru(II),Rh(III) bimetallics, differing only in the terminal ligands. 61 It was found that the first two reductions displayed electrochemical irreversibility, indicating an electrochemical reduction followed by rapid halide loss. The irreversibility of these Rh III/II and Rh II/I also varies with potential scan rate, providing mechanistic insight into the systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthesis of Ru II ‐Rh III : [(phen) 2 Ru(dpp)RhCl 2 (phen)](PF 6 ) 3 was synthesized through a building block approach (Scheme S1) based on previously reported methods for Ru II ,Rh III bimetallics modified as follows . [RhCl 3 (phen)(DMF)] (60.9 mg, 0.132 mmol) was dissolved in warm ethanol/water 2:1 (10 mL), and a solution of [(phen) 2 Ru(dpp)](PF 6 ) 2 (110 mg, 0.112 mmol) in the same solvent mixture (10 mL) was added slowly.…”
Section: Methodsmentioning
confidence: 99%